Identifikasi Perkembangan Bahasa Keaksaraan Anak Kelompok A di TK Raudatush Shibyan Ampenan - Dian Fakhira; Fahruddin Fahruddin; Ika Rachmayani; Baik Nilawati Astini (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this study was to identify the development of language literacy for group A children at Raudatush Shibyan Ampenan Kindergarten in the 2021/2022 academic year. This type of research is descriptive qualitative. The method of data collection in this research is by observation, interviews, and documentation using research instruments that have been prepared. Data analysis in this research is descriptive qualitative using data analysis model Miles and Huberman with percentage formula. The results of the acquisition of the percentage of research identifying the development of literacy language development of children in group A are as follows: of the 15 children studied who have criteria for developing undeveloped literacy language as many as 9 children with a percentage of 50.3%, then the criteria for developing language literacy begin to develop as many as 3 people children with a percentage of 25.4%, and the criteria for developing language literacy developed as expected as many as 3 children with a percentage of 24.2%. Recognizing letter symbols has begun to develop to reach 68%, recognizing the sounds of animals or objects around them reaches 36%, making meaningful scribbles reaches 38%, imitating (writing and speaking) letters A-Z reaches 49% development. Based on the percentage results obtained, it can be concluded that the development of the language literacy of group A children at Raudatush Shibyan Ampenan Kindergarten in the 2021/2022 academic year has not yet developed